ANALYSIS OF DEGREES OF REGIONAL ORIGINAL INCOME DECENTRALIZATION AND INDEPENDENCE AND THE RELATIONSHIP WITH REGIONAL EXPENDITURE PRODUCTIVITY IN MAGELANG REGENCY 2016-2020 - Arma Riski Nur Cahyani; Nuwun Priyono (Transpublika Publisher, 2022)
This research aims to (1) examine the level of fiscal decentralization degrees in Magelang Regency, (2) examine the level of financial independence in Magelang Regency, (3) examine the level of regional expenditure productivity of Magelang Regency, (4) examine the relationship of decentralization degrees and independence of fiscal with regional expenditure productivity in Magelang Regency. This research uses secondary data in the form of time series from 2016-2020 consisting of the realization of Magelang Regency APBD (Regional Revenue and Expenditure Budget), the realization of Magelang Regency PDRB (Local Gross Domestic Product (GDP)). In analyzing this study using the analysis of the Degree of Fiscal Decentralization (DDF), the analysis of the Degree of Fiscal Independence (DKF), the analysis of Regional Expenditure Productivity (PBD), and the Pearson Correlation analysis. The results showed that DDF value of 10,62, DKF value of 12,18, and PBD of 18,38, all three calculations were in low category. Therefore, the findings shows that there is a negative relationship that is relatively strong and real.